PROFIL TIPE TESTIMONIAL ONLINE PADA PRODUK KOMPUTER TERHADAP SIKAP ATAS IKLAN & SIKAP ATAS PERILAKU MEMBELI - Fickar Suryadinningrat (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2012)
Abstract With increasing, product line sales consumers not only in the real world of shopping mall, or the department store now the use of technology enables the consumer can do shopping activity over the internet.With just open, computer facility and typed site desired then transaction activity can be done.Still many consumers have limited in doing online activities shopping. Consumers like shopping buying clothes, sometimes only online electronics and computer. Consumer spending often doing online activities can diperngaruhi by a variety of factors, among other activities, product interesting advertising mounted coquet.Advertising is a process involving communication sponsor certain.Testimonials is part of an advertising, any type testimonials advertising surveyed: experts, celebrity and ordinary people. Testimonials through the ad will impact consumers, to attitude this attitude can be attitude toward advertising, attitude toward brands, attitude toward behavior.This research purposes to perceive the difference between profile type testimonials other experts, artist, and people ordinary online on the computer products with the advertising and attitudes of behavior membeli.metode used in this research is research methods descriptive. These studies have samples 32 responden. From this research result that there are differences type testimonials online at the computer products with the advertising and attitudes of behavior buy.Turns experts has a higher value than artist and ordinary people.even though artist had a low value on advertising and with the attitude of behavior buy.Researchers assumed that experts have preference better in the use of computers on celebrities and ordinary people. Key word : Type Testimonials , Attitude toward advertising, Attitude towards Behavior of buy